Current status and clinical applications of tissue engineering of the gastrointestinal tract: a systematized narrative review - Liu, Yilin; Chong, Lynn; Read, Matthew (Frontiers in Gastroenterology, 2023)
Background Since the advent of regenerative medicine, tissue engineering of the gastrointestinal tract (GIT) has been extensively studied in laboratory animals and humans. Various biologic scaffolds and cell sources have been trialed to repair or reconstruct different GIT defects. Achievements in this field have led to novel approaches in curing GIT diseases and circumventing the morbidity-related complications associated with current therapy. Objective This review aims to describe recent advances in GIT tissue engineering, with an emphasis on technologies with potential for clinical use. Methods A literature search was conducted in Ovid MEDLINE® ALL for relevant studies (2000–September 2023) using the keywords “tissue-engineering”, “scaffolds”, “organoids”, “cell-therapy”, “esophagus”, “stomach”, “small intestine”, “colon”, “rectum”, and “anus”. Articles were included if they were in vivo animal studies or clinical studies written in English that investigated tissue engineering for treating GIT defects. Results A total of 836 articles were identified in the initial search. Following duplicate removal, abstract, and full-text screening, 48 articles were included in the final review. Many studies on esophageal defects thus far have described the success of covering partial-thickness defects with autologous cell sheets and closing full-thickness defects with decellularized scaffolds in both animals and humans. A limited number of reports have also demonstrated the de novo organogenesis of the esophagus to repair short-segment circumferential esophageal defects with autologous pluripotent cells and scaffolds. In the stomach, multiple animal studies have reported on the feasibility of gastric epithelium regeneration using multipotent cells and/or scaffolds to correct partial- and full-thickness defects. One study observed the regeneration of whole-layer stomach defects using the organoids-on-polymer approach. Similarly, in the intestine, pluripotent cells and scaffolds were shown to effectively repair both partial- and full-thickness defects. Animal experiments have produced tissue-engineered small intestines (TESI) with the organoids-on-polymer approach. Furthermore, in the rectum and anus, mesenchymal stem cell therapies with or without bioscaffolds have shown promise for treating full-thickness defects, as demonstrated in multiple human trials. Conclusion Tissue-engineering approaches for repairing various types of GI defects in the esophagus, stomach, intestines, rectum, and anus have been extensively explored in animal models, with promising outcomes. Moreover, successful human trials have demonstrated the feasibility of reconstructing esophageal, rectal, and anal defects using these innovative approaches. Technologies such as mesenchymal stem cells, decellularization, organoids, and cell sheets are the most promising and closer to clinical translation. Collaboration between gastrointestinal surgery and regenerative medicine is expected to bring about novel therapeutic modalities in the future.